A Comparison of Intravenous Esmolol versus Intravenous Diltiazem in Atrial Fibrillation with Rapid Ventricular Response-A Study from An Academic Center - Regmi, Manjari R; Al-Akchar, Mohammad; Bhandari, Bishal; Ibrahim, Abdisamad M; Parajuli, Priyanka; Garcia, Odalys Estefania Lara; Al-Bast, Basma; Tandan, Nitin; Maini, Ruby; Skoza, Warren Alexander; et al. (Cardiology and Cardiovascular Medicine, 2020)
Introduction: This study’s objective was to compare the differences in the effects of intravenous esmolol and diltiazem on patients having atrial fibrillation with RVR. Methods: The measured parameters were the number of hospital re-admissions, length of hospital stay, time taken for rate control, and side effects like hypotension and pacemaker use. This retrospective cohort study included all adult patients with A-fib with RVR treated with IV esmolol and diltiazem from an academic center between 2016-2018. Patients who were on rhythm control or required cardioversion within 24 hours were excluded. Categorical and continuous outcomes were compared with chi-square and t-tests respectively. Cox-regression was used for the length of hospital-stay and time taken for rate control and the hazard ratio was reported. For the number of hospital re-admissions, linear regression was used. Results: Of 841 A-fib patients, the eligible sample size was 60 (diltiazem: 48 and esmolol: 12). The average time taken for rate control was 1654 ± 726 minutes for esmolol and 1072 ± 241 minutes for diltiazem, length of hospital-stay was 9 ± 2.16 days for esmolol and 7.98 ± 1.53 days for diltiazem, and the number of hospital re-admissions were 1.67 ± 0.31 for esmolol 2.69 ± 0.42 for diltiazem. A hazard ratio of esmolol with reference to diltiazem was 0.89 (CI: 0.45-1.76) for the time taken for rate control and 0.99 (CI: 0.50-1.97) for the length of hospital stay. 20.83% of patients were hypotensive on diltiazem and none on esmolol (p-value: 0.194). Conclusion: Although observations based on our small unmatched retrospective study for the measured parameters showed a superiority trend for esmolol, especially with regards to less hypotension, the differences were not statistically significant.